2018
DOI: 10.1007/s11266-018-0016-9
|View full text |Cite
|
Sign up to set email alerts
|

Entrepreneurial NPOs in Russia: Rationalizing the Mission

Abstract: Nonprofit organizations in Russia are introducing for-profit activities as a means of gaining autonomy from external donors, and as instruments of strategic planning and sustainable development. This study focuses on organizations that work with welfare provision and explores how they reconcile entrepreneurial activities with their social mission. More specifically, we interrogate how two institutional logics, business and nonprofit, are defined and reconciled in organizational identities, structures and hiera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 48 publications
(57 reference statements)
0
7
0
1
Order By: Relevance
“…While acknowledging the existence of different forms of managerialism (Dobrai & Farkas, 2016), researchers have concluded that there are both positive and negative consequences of adopting business strategies and tools in NPOs (Maier et al, 2016; Shirinashihama, 2018). Generally, research has shown that the effects of managerialism depend on how an organization reacts to competing institutional norms, namely their nonprofit character and certain for‐profit tools or practices (Kravchenko & Moskvina, 2018). After all, when faced with managerialization of their processes and cultures, organizations are challenged to accommodate both their mission‐driven “normative” identity and a new, commercial “utilitarian” identity (Lee & Bourne, 2017, p. 796).…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…While acknowledging the existence of different forms of managerialism (Dobrai & Farkas, 2016), researchers have concluded that there are both positive and negative consequences of adopting business strategies and tools in NPOs (Maier et al, 2016; Shirinashihama, 2018). Generally, research has shown that the effects of managerialism depend on how an organization reacts to competing institutional norms, namely their nonprofit character and certain for‐profit tools or practices (Kravchenko & Moskvina, 2018). After all, when faced with managerialization of their processes and cultures, organizations are challenged to accommodate both their mission‐driven “normative” identity and a new, commercial “utilitarian” identity (Lee & Bourne, 2017, p. 796).…”
Section: Literature Reviewmentioning
confidence: 99%
“…As described in the previous section, isomorphic pressures are responsible for homogenization of the nonprofit sector (Dolnicar et al, 2008; Frumkin & Galaskiewicz, 2004; Meyer & Rowan, 1977; Ramanath, 2009), with organizations increasingly adopting business tools and practices in a process described as managerialism (Maier et al, 2016). This managerialization of organizations can boost organizational performance (Duque‐Zuluaga & Schneider, 2008; Shirinashihama, 2018), but brings with it a risk of mission drift (Eikenberry & Kluver, 2004; Jones, 2007), depending on how an organization reacts to different or even competing institutional logics (Kravchenko & Moskvina, 2018). We, therefore, hypothesize that mimetic, normative, and coercive isomorphic pressures affect organizations distinctively in terms of performance and mission drift via managerialism.…”
Section: Hypothesesmentioning
confidence: 99%
“…The power of NPOs derives from collective group membership and a high degree of social trust. NPOs can bring, for example, environmental or social expertise and-as a result of public trust-legitimacy into cross-sector social partnerships (Kravchenko and Moskvina 2018;Thornton 2004;Van Huijstee et al 2011).…”
Section: Cross-sector Social Partnerships and Institutional Logicsmentioning
confidence: 99%
“…Since 2011-2012, the publications have tended to focus on cataloguing and analyzing exemplary cases, as well as on attempts to create empirically proven typologies and classifications (Moskovskaya, 2011;Aray and Burmistrova, 2014;Vetrova, 2015;Nefedova, 2015). The latest publications focus on the role of social entrepreneurship in society, its institutional context and the legitimacy of social entrepreneurship in Russia (Moskovskaya and Soboleva, 2016;Moskovskaya et al, 2017;Kravchenko and Moskvina, 2018). Demand has led to some works combining empirical evidence with teaching materials (Zvereva, 2015;Blagov, 2017).…”
Section: Sej 152 158mentioning
confidence: 99%